THE DIFFERENCE BETWEEN WORK STRESS BEFORE AND AFTER SPIRITUAL EMOTIONAL FREEDOM TECHNIQUE (SEFT) THERAPY - David Martua Sehat Nababan; Decy Situngkir; Ira Marti Ayu; Ahmad Irfandi (Faculty of Vocational Studies, Universitas Airlangga, 2025)
Background: Nurses are susceptible to work stress caused by conflicts with coworkers and superiors, as well as uncertainty about the effects of therapy on patients. The preliminary study results on 15 nurses showed that 11 nurses (73%) experienced moderate stress, while four nurses (27%) experienced severe stress. Purpose: This research aims to analyze the differences before and after Spiritual Emotional Freedom Technique (SEFT) therapy in reducing nurses’ stress. Method: This study applied a quantitative approach, utilizing a pre-experimental design with a one-group pre-post test design involving 36 nurses before and after SEFT therapy. Sampling was conducted using a total sampling technique. The study was carried out from July to August 2021, using the Occupational Stress Inventory-Revised Edition (OSI-R) questionnaire. A Paired Sample T test was utilized as the statistical test. Result: The univariate test results for work stress before and after SEFT therapy were 77.75 and 71.11, respectively. The bivariate test, with p-value of 0.001, revealed differences in work stress scores before and after SEFT therapy for nurses. Conclusion: SEFT therapy can reduce the stress of nurses at Hospital A. Therefore, the hospital management needs to implement SEFT therapy to reduce work-related stress for the nurses.